Teoria da decisão: estrutura e dinâmica das bases filosóficas da interpretação jurídica - Suárez, Nuria López Cabaleiro (2013)
This dissertation has its start point in the dichotomy pointed by Thomas Kuhn that places law always between the internal development of its own science (attending to the legal norm, auto reference) and attending social demands (will of Constitution; fundamental rights, theory of justice, in other words, hetero references). For this purpose, analyses in a historical the philosophical grounds of the thesis on legal interpretation with higher impact, to search for a paradigmatic solution, in line with the recent philosophy of science and with the models of subject after the linguisticpragmatic turn. Concludes for the adoption of the subject as the philosophical center of decision theory e presents its dynamic from the viewpoint of game theory